2015
DOI: 10.2131/jts.40.263
|View full text |Cite
|
Sign up to set email alerts
|

Induced adverse effects of prenatal exposure to silver nanoparticles on neurobehavioral development of offspring of mice

Abstract: Steadily increased use of silver nanoparticles (Ag-NPs), has increased the amount of its exposure to humans and animals. Current scarce knowledge about the influences of prenatal exposure to Ag-NPs on postnatal outcomes, motivated us to investigate whether being exposed to it during pregnancy has any effects on neurobehavioral development of the adult offspring. Thirty virgin female NMRI mice were mated and treated subcutaneously once every three days from gestation day 3 until delivery, by 0, 0.2 and 2 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 68 publications
(86 reference statements)
1
33
1
Order By: Relevance
“…Coating with PVP protected offspring from the toxic effects of Ag-NPs in that study [ 45 ]. Ghaderi et al reported that subcutaneous injection of Ag-NPs during pregnancy could induce adverse consequences on neurobehavioral development of offspring because of its damage on spatial cognition [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coating with PVP protected offspring from the toxic effects of Ag-NPs in that study [ 45 ]. Ghaderi et al reported that subcutaneous injection of Ag-NPs during pregnancy could induce adverse consequences on neurobehavioral development of offspring because of its damage on spatial cognition [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors argued that this finding might be due to facilitation of aggregates at higher gut concentrations, preventing internalization via the gastrointestinal tract and thereby reducing fetotoxicity at higher doses [ 16 ]. The potential negative effects of Ag NPs on development and reproduction have yet to be fully clarified [ 17 ]. In comparison, only one rodent study has investigated the developmental toxicity of orally administered ionic silver (190 mg kg/day) on gestational day 1–20.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to remember that the placenta is not just a filter protecting the developing fetus from maternal blood substances, but also plays an important role in, for example, in fetal brain development (Bonnin and Levitt, 2012;Hsiao and Patterson, 2012;Zeltser and Leibel, 2011). The internal concentration of silver in the placenta might point to the mechanisms behind the reported impact on fetal brain and neurological development after prenatal AgNP exposure (Lale Ataei and Ebrahimzadeh-bideskan, 2014;Ganjuri et al, 2015;Ghaderi et al, 2015;Wu et al, 2015). Circulating biomarkers like selected pro-and anti-inflammatory cytokines and chemokines were analyzed in the plasma of pregnant rats to understand possible correlations with nanosilver exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Wu and colleagues also found that offspring at postnatal day 35 performed less well in the Morris Water Maze, suggesting impaired spatial cognition in rat offspring following prenatal exposure (Wu, et al 2015). Postnatal neurobehavioral disorders as a resulting from prenatal exposure to AgNP has also been reported in mice (Ghaderi, et al 2015). …”
Section: Introductionmentioning
confidence: 98%
“…In vitro and in vivo studies also suggest that AgNPs can induce transcriptomic and non-coding RNA changes in neuronal cells and various brain regions, especially the hippocampus [12][13][14][15][16][17][18][19][20] . Behavioral disruptions, especially in cognitive functions, potential anxiogenic effects, depression-like behaviors, and altered activity levels, have been reported after direct or developmental exposure of rodents and zebrafish to AgNPs 12,13,[21][22][23][24][25] . Other observed neurotoxicological effects include increased permeability of the blood-brain-barrier (BBB), edema formation, neuronal degradation and apoptosis, synaptic degeneration, tight junction disruptions, increase in reactive oxygen species (ROS), amyloid-β (Aβ) plagues, and astrocyte swelling 15-18, 20, 22, 23, 26-31 .…”
mentioning
confidence: 99%